Concepts of occupational therapy - Reed, Kathlyn L., ....-; Sanderson, Sharon Nelson, ....- (Baltimore : Lippincott, Williams and Wilkins, 1999)
Contents:---------1. The philosophical base. 2. The conceptual base. 3. The consumer domain base. 4. The models base. 5. The knowledge base. 6. The skills base. 7. The practice base. 8. The contextual base. 9. Professional literature base. 10. Case studies and discussion questions. 11. Appendixes
Keywords: Ergotherapie -- Methodiek; Ergotherapie